2019
DOI: 10.1109/access.2019.2921808
|View full text |Cite
|
Sign up to set email alerts
|

Study of Propagation Channel Characteristics for Underwater Acoustic Communication Environments

Abstract: For the study of propagation characteristics in underwater acoustic channels, a geometrybased model is introduced to represent the multipath scattering environments between a transmitter (Tx) and a mobile receiver (MR). To consider the impact of the scattering environments on the propagation characteristics with low complexity, we adopt a rectangle to describe the communication environments of the vertical cross section of the ocean, where the scatterers are assumed to be randomly distributed on the surface an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…In other words, it is not possible to design an accurate channel model for universal employment in every application [50]. On the other hand, a feasible model has to undergo some degrees of simplifications, which is strongly correlated with the requirements of the problem itself [81]. As an example, we might simply neglect the water salinity in an acoustic channel model, while this simplification is not possible in underwater electromagnetic propagation.…”
Section: E Underwater Channel Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, it is not possible to design an accurate channel model for universal employment in every application [50]. On the other hand, a feasible model has to undergo some degrees of simplifications, which is strongly correlated with the requirements of the problem itself [81]. As an example, we might simply neglect the water salinity in an acoustic channel model, while this simplification is not possible in underwater electromagnetic propagation.…”
Section: E Underwater Channel Modelingmentioning
confidence: 99%
“…This is not the same for optical waves, as will be studied in Section III-B2. In a relevant study, Zhou et al [81] have considered the impact of the scattering particles on the propagation characteristics of acoustic waves in underwater environments. They randomly distribute those particles on an assumptive rectangular cross section of ocean.…”
Section: E Underwater Channel Modelingmentioning
confidence: 99%
“…However, designing a high-speed, reliable, and low-power UWA communication system is challenging. Zhou et al [ 3 ] derived underwater statistical propagation characteristics using closed-form probability density functions for calculating the angle of departure and arrival. The spatial and frequency correlation functions of two different UWA propagation paths were explored.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that can be found in the literature about acoustic modems include: Location algorithms [14,15], channel estimation [16,17], performance analysis [18,19], and implementation techniques [20,21]. At this point, it is important to note that most of these and other studies [22,23] consider the use of the Orthogonal Frequency Division Multiplexing (OFDM) as the main waveform for transmitting the information.…”
Section: Introductionmentioning
confidence: 99%